Mosaic Form of Turner Syndrome - Laqif, Abdurahman; Wijayanti, Agung Sari; Moelyo, Annang Giri; Budihastuti, Uki Retno; Melinawati, Eriana (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To report a case of breast growth disorder in a mosaic form of Turner Syndrome. Turner syndrome is a chromosomal condition characterized by small height and primary ovarian insufficiency that affects one in every 2500 female births. Mosaicism is likely to occur when monosomy X develops in only a few cells during development. The clinical presentation of Turner syndrome mosaicism is atypical, with symptom severity varying based on the number of affected cells. This case discusses issues with secondary sex development, including mild hyperandrogenism, and explores how combination hormonal treatment can aid in enhancing secondary sex development. Method: Case Report. Case: A 21-year-old woman presented with chief complaint of the lack of breast enlargement. She exhibited normal genitalia internally and externally and had a regular menstrual cycle. Karyotyping revealed a mosaic pattern of 45, X/46, XX (1 percent/99%) with normal estradiol levels and elevated testosterone levels (indicating mild hyperandrogenism). The patient underwent two cycles of hormone therapy using Ethinyl Estradiol and Drospirenone, resulting in breast growth progression from Tanner stage 1 to Tanner stage 2. Conclusion: Mosaicism in Turner syndrome is plausible, and the severity of clinical symptoms correlates with the number of defective chromosomes. The presentation of Turner syndrome mosaicism varies, and therapy should be tailored to address specific symptoms. While breast development is observed in some girls with Turner Syndrome, instances of breast growth disorder may occur, involving estrogen activity and estrogen receptor sensitivity. Although the exact cause of impaired breast growth remains unknown, administering estrogen in such cases can improve secondary sexual characteristics. Keywords: mild hyperandrogenism, mosaicism, turner syndrome